2019
DOI: 10.1080/14740338.2019.1669559
|View full text |Cite
|
Sign up to set email alerts
|

Making medicines safer: analysis of patient reports to the UK’s Yellow Card Scheme

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Our results are consistent with previous studies that have shown that public awareness and uptake of the Yellow Card scheme is low generally [5][6][7]. Yet, both survey and focus group participants mostly agreed that patients had a significant role to play in reporting ADRs and, when made aware about the Yellow Card scheme, responded positively.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with previous studies that have shown that public awareness and uptake of the Yellow Card scheme is low generally [5][6][7]. Yet, both survey and focus group participants mostly agreed that patients had a significant role to play in reporting ADRs and, when made aware about the Yellow Card scheme, responded positively.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…Despite the Yellow Card scheme being open to the public since 2005, there still remains significant under-reporting of ADRs. Low public awareness may be part of the problem [5,6]. A study in 2009 found that fewer than one in ten people had heard of the scheme and, even when made aware, people expressed uncertainty about the value of their reports to the MHRA [7].…”
Section: Online Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…There are two major forms of post-marketing drug surveillance. Some are formed by government regulators such as the Vaccine Adverse Event Reporting System (VAERS) by the United States Food and Drug Administration [6] or the Yellow Card Scheme by the United Kingdom Medicines and Healthcare Products Regulatory Agency [7]. Also, public/private organizations have a system to monitor drug side-effects such as the Research on Adverse Drug events And Reports and various websites [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some are formed by government regulators such as the Vaccine Adverse Event Reporting System (VAERS) by the United States Food and Drug Administration 6 or the Yellow Card Scheme by the United Kingdom Medicines and Healthcare Products Regulatory Agency. 7 Also, public/private organizations have a system to monitor drug side-effects such as the Research on Adverse Drug events And Reports. 8 Existing methods for identifying adverse events typically focused on analyzing molecular drug composition, 9 query logs, 10 VAERS records, 11 or clinical notes in the medical records 12 but did not analyze specifically the sentiment of the consumers using their reviews of the drug.…”
Section: Introductionmentioning
confidence: 99%